2022
DOI: 10.3390/agronomy12112630
|View full text |Cite
|
Sign up to set email alerts
|

Yield Predictions of Four Hybrids of Maize (Zea mays) Using Multispectral Images Obtained from UAV in the Coast of Peru

Abstract: Early assessment of crop development is a key aspect of precision agriculture. Shortening the time of response before a deficit of irrigation, nutrients and damage by diseases is one of the usual concerns in agriculture. Early prediction of crop yields can increase profitability for the farmer’s economy. In this study, we aimed to predict the yield of four maize commercial hybrids (Dekalb7508, Advanta9313, MH_INIA619 and Exp_05PMLM) using vegetation indices (VIs). A total of 10 VIs (NDVI, GNDVI, GCI, RVI, NDRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Poor early season performance was also found in other corn yield prediction studies [29,75,76,84]. Saravia et al [85] found that imagery from the reproductive growth stage (mid season) had the most correlation with yield. Sunoj et al [30] also found that at the very end of the season (R5) yield prediction performance was considerably lower.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Poor early season performance was also found in other corn yield prediction studies [29,75,76,84]. Saravia et al [85] found that imagery from the reproductive growth stage (mid season) had the most correlation with yield. Sunoj et al [30] also found that at the very end of the season (R5) yield prediction performance was considerably lower.…”
Section: Discussionmentioning
confidence: 70%
“…Barzin et al [79] used ML models that include multi-VI features and found that (a) the Simplified Canopy Chlorophyll Content Index (SCCCI), where SCCCI = NDVI RedEdge /NDVI, was one of the best VIs for predicting yield at various growth stages; (b) the V10 and VT growth stages were the best growth stages for model performance. Saravia et al [85] compared model performance when using multi-VI feature datasets vs. single-VI feature datasets. They found a high correlation between multiple VIs and yield during the reproductive growth stage of corn.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported growth indicators and vegetation indices as reliable predictors for yield prediction in various crops [ 7 , 16 , 34 ]. However, the prediction accuracy of seed yield varied when utilizing data collected at different growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…Changes observed in the spectral signature at 25% severity when compared to healthy leaves can provide early information on the biochemical changes in the leaf caused by the disease, and the use of a hyperspectral sensor is essential for implementing effective strategies to diagnose target spot and prevent major crop losses [36]. Furthermore, VIs calculated from the reflectance of the VIS and NIR bands can provide more accurate estimates of chlorophyll content, ensuring accurate results regarding the plant's photosynthetic activity [40].…”
Section: Discussionmentioning
confidence: 99%